Cournot Oligopoly With Uncertain Entry - Kamien, Morton I.; Schwartz, Nancy L. (Review of Economic Studies, 1975)
Morton I. Kamien, Nancy L. Schwartz; Cournot Oligopoly With Uncertain Entry12, The Review of Economic Studies, Volume 42, Issue 1, 1 January 1975, Pages 125–131